Cost pass-through with capacity constraints and international linkages - Reinhard Ellwanger; Hinnerk Gnutzmann; Piotr Śpiewanowski (Bank of Canada, 2023)
Commodity markets are linked through international trade but are separated by heterogeneous regulations and input markets. We investigate theoretically and empirically how regional, as opposed to global, cost shocks pass through into global prices. Capacity constraints mitigate the output response to regional cost shocks in the short run. Once constraints bind, the pass-through of a cost increase is enhanced while for cost decreases it drops to zero. We study the market for ammonia, a commodity produced largely from natural gas, to highlight the nonlinearity of the cost pass-through and its implications for unilateral climate policies.
Keywords: L13; L65; Q54; Q40; 330; Climate change; International topics; Inflation and prices; Econometric and statistical methods